Prediksi masa simpan emulsi virgin coconut oil-sari jeruk berdasarkan perubahan bilangan peroksida menggunakan metode accelerated shelf-life testing - Zakir Sabara; Lastri Wiyani; G Gusnawati; Andi Aladin; Vita Febrianti Mansyu; Chusnul Azzahrah (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2026)
Virgin Coconut Oil–Orange Juice Emulsion (EVCO-SJ) is formulated by mixing Virgin Coconut Oil with Orange Juice and other additives. EVCO-SJ was developed as an alternative form of VCO consumption to reduce the oily sensation in the mouth when consuming VCO directly. Determining the product's shelf life is a crucial aspect because it is closely related to determining the expiration date of food products. This study aims to predict the shelf life of EVCO-SJ based on changes in peroxide value using the Accelerated Shelf-Life Testing (ASLT) method. EVCO-SJ is made by mixing VCO and orange juice (8:2) using gum arabic (0.75%) as emulsifier and homogenized using a Tokebi device at 23,000 rpm for 2 minutes. EVCO-SJ is stored at three temperature variations, namely 30 °C, 45 °C, and 55 °C, with storage time intervals of 0, 7, 14, 21, 28, and 35 days. The observed quality parameter is the peroxide value as an early indicator of lipid oxidation. Data on changes in peroxide value are analyzed using the Arrhenius model in the ASLT method to predict shelf life. The results showed that increasing storage temperature accelerated the rate of lipid oxidation in EVCO-SJ, as indicated by an increase in the peroxide value during storage. Predicted shelf life of EVCO-SJ based on the ASLT method indicated that the shelf life at 30°C, 45°C, and 55°C was 146.34 days, 83.46 days, and 59.06 days, respectively. These results provide scientific information regarding the oxidative stability of EVCO-SJ and can serve as a basis for determining shelf life and developing VCO-based emulsion products with measurable quality and shelf life.